Intermediate Acts of Incorporation: Body, Psychogeography, and Drift in Arts with Electronic Technologies - Monreal Ramírez, Jesús (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
In this article, I explore the rupture between the regime of the body as a performative device and the regime of the body defined by what I call an intermediate act of incorporation: an expression to designate acts in which a medium updates its material presence, with its own rules, by transfer with another medium in a way that enables the real capacities of communication and cognition. This process tells us about an ontological and epistemological dimension of intermediality.